Wage posting or wage bargaining? Evidence from the employers side - Hermann Gartner; Hanna Brenzel; Claus Schnabel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Using a representative establishment dataset, this paper analyzes the incidence of wage posting and wage bargaining in the matching process. We show that both modes of wage determination coexist in the German labor market, with about two-thirds of hirings being characterized by wage posting. Wage posting dominates in the public sector, in larger firms, in firms covered by collective agreements, and in part-time and fixed-term contracts. Job-seekers who are unemployed, out of the labor force or just finished their apprenticeship are also less likely to get a chance of negotiating. Wage bargaining is more likely for more-educated applicants and in jobs with special requirements as well as in tight regional labor markets.
Keywords: E24; J30; J63; 330